Influence of aggressive environment on wear of tires of wheels of a car - Герасименко, Віталій Григорович; Губа, Вікторія Вікторівна (Eastern-European Journal of Enterprise Technologies, 2013)
Operation of roadway surfaces shows that the maximum roughness of a surface layer reduces the possibility of emergence of the ”soap effect” in the zone of ”treadmill”, especially during the deposition of fog or storm water on the surface. Such deposition of particles may be a reason of accidents or may enlarge the conditions of their occurrence. The article concerns the question of improvement of a driver’s working conditions, the properties of tires, transverse and longitudinal sloping of the surface at annual operation of roads and a car. Operation of car tires leads to wear of a tread of a car wheel. Galling leads to additional wear, which can be significant in certain conditions (frequent stops, drops, crossroads, tram and railway crossings). The process of reshaping of a microprofile is very diverse and its changes occur gradually and depend on many factors. Each layer of wear requires special assessment on the following: static evaluation within local profile, taking into account the midline, which takes into account size and shape of surface appearances.